Effect of transport and delayed analysis on hematological variables in blood samples taken from elite speed skaters - Kuipers, H.; Dubravcic-Simunjak, S.; Moran, J.; Mitchell, D.; Shobe, J.; Sakai, H.; Ambartsumov, R. (Croatian Sports Medicine Journal, 2007)
To study the effect of transport and storage on the stability of hematological variables, two blood samples from 81 elite short track speed skaters were analyzed within four hours after sampling. One sample was analyzed again 24 hours later. After analysis, the second sample was subjected to road and air transport and analyzed a third time 24 hours after the second analysis. To study the effect of storage up to 48 hours, one blood sample was taken from each of 81 elite long track speed skaters and subsequently analyzed within four hours after sampling, and again after 24 and 48 hours. Transporting the blood samples and storing them for 24 hours did not significantly change hemoglobin concentration and % reticulocytes. Hematocrit and the difference between total measured hemoglobin and cellular hemoglobin concentration were increased after 24 hours (p<0.01). In samples stored for 48 hours, hemoglobin concentration remained stable for up to the entire 48-hour time period. In contrast, after 24 hours the mean cellular volume (MCV) increased (p<0.05). After 48 hours hematocrit (p<0.05), percentage and number of reticulocytes increased 48 hours after sampling (p<0.01). In conclusion, hemoglobin concentration and percentage of reticulocytes may remain stable for up to 24 hours after sampling, while hematocrit may increase during this time period. Furthermore, hematocrit, MCV, and percentage and number of reticulocytes may also rise during the 24 hours after sampling. However, when transport is involved hemolysis may occur.